2018
DOI: 10.1590/2179-8087.004516
|View full text |Cite
|
Sign up to set email alerts
|

Soil Compaction Due to Wood Harvesting Traffic at Different Extraction Distances

Abstract: This study evaluated the effect on Oxisol soil compaction of traffic by wood harvesting machines from different extraction distances carried out by a logging company located in Paraná State. The harvesting system was composed of a feller buncher, skidder and harvester, in which soil compaction was evaluated at four extraction distances and four depths by means of density, porosity and soil penetration resistance. Increased machine traffic resulted in the highest compaction in the soil surface layers on the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The extent of machine turning can also influence the severity of soil disturbances, particularly when the change in direction is pronounced [63]. Driving distances within a harvest site could also have an impact on the extent and severity of compaction or rather, that all traffic is funneled to landing sites leads to higher soil compaction at the perimeters of harvest sites [64].…”
Section: Reduced Compaction By Improved Planningmentioning
confidence: 99%
“…The extent of machine turning can also influence the severity of soil disturbances, particularly when the change in direction is pronounced [63]. Driving distances within a harvest site could also have an impact on the extent and severity of compaction or rather, that all traffic is funneled to landing sites leads to higher soil compaction at the perimeters of harvest sites [64].…”
Section: Reduced Compaction By Improved Planningmentioning
confidence: 99%
“…Szymczak et al (2014) argue that it may occur a dissipation of the pressure applied by the traffic of the machines in the soil, not reaching the deeper layers to a considerable level. Rodrigues et al (2018) observed an increase in density and decrease in soil porosity in the soil surface layers after machine traffic in the harvest of Eucalyptus grandis, with values above critical limits in the tracks of machine traffic.…”
Section: Discussionmentioning
confidence: 86%
“…), limitation of adsorption and absorption of nutrients by plants (RICHART et al, 2005). Besides the change in porosity, it results in decrease of pore size (SAMPIETRO; LOPES, 2016) and increase in the values of soil resistance to penetration (RODRIGUES et al, 2018). FLORESTA, Curitiba, PR, v. 50, n. 4, p. 1837-1843 Dias Junior et al (2005) warn that one of the limitations to achieve sustainable forest development is related to the machines traffic during harvesting and wood transshipment operations.…”
Section: Introductionmentioning
confidence: 99%
“…The density increase recorded for the mechanized CTL treatment was significantly higher than for the manual CTL treatment. As soil compaction is highly complex and a very recent research topic [46][47][48][49][50], further analysis should be conducted if this indicator is of crucial importance.…”
Section: Discussionmentioning
confidence: 99%